2019
DOI: 10.1158/1535-7163.mct-18-1206
|View full text |Cite
|
Sign up to set email alerts
|

SF2523: Dual PI3K/BRD4 Inhibitor Blocks Tumor Immunosuppression and Promotes Adaptive Immune Responses in Cancer

Abstract: Macrophages (MÂs) are key immune infiltrates in solid tumors and serve as major drivers behind tumor growth, immune suppression, and inhibition of adaptive immune responses in the tumor microenvironment (TME). Bromodomain and extraterminal (BET) protein, BRD4, which binds to acetylated lysine on histone tails, has recently been reported to promote gene transcription of proinflammatory cytokines but has rarely been explored for its role in IL4driven MÂ transcriptional programming and MÂ-mediated immunosuppressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…Another target for negative regulation of antitumor immunity recently discovered and reported by our group and other laboratories is the PI3K signaling pathway, in particular p110g in MÈs (6,17). Our laboratory has reported that p110g in MÈs promotes expression of protumorigenic MÈs in TME and our pan PI3K/BRD4 inhibitor SF1126 or SF2523, blocked tumor growth and MÈ-mediated immunosuppression in tumors (17,18). Furthermore, Syk kinase is required for activation of PI3K in MÈs and B cells (19,20).…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Another target for negative regulation of antitumor immunity recently discovered and reported by our group and other laboratories is the PI3K signaling pathway, in particular p110g in MÈs (6,17). Our laboratory has reported that p110g in MÈs promotes expression of protumorigenic MÈs in TME and our pan PI3K/BRD4 inhibitor SF1126 or SF2523, blocked tumor growth and MÈ-mediated immunosuppression in tumors (17,18). Furthermore, Syk kinase is required for activation of PI3K in MÈs and B cells (19,20).…”
Section: Introductionmentioning
confidence: 67%
“…2A). In contrast, expression of immunostimulatory genes (6,18) was significantly enhanced in the TAMs from Syk MC-KO animals compared with that of Syk MC-WT tumors ( Fig. 2A).…”
Section: Syk Kinase Promotes Mè Polarization and Immunosuppressionmentioning
confidence: 91%
See 3 more Smart Citations